Analisa Produktivitas Kerja Karyawan Bagian Produksi Ditinjau Dari Aspek Lingkungan Kerja, Kesehatan dan Keselamatan Kerja (K3) - Shafa Aurelia Azzahra; Nurhidayah Nurhidayah; Eris Dianawati (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine how the influence of the work environment, occupational health and safety (K3) on the work productivity of employees in the production division of PT Mega Prakarsa Engineering Indonesia Sidoarjo. The population used in this study were 45 employees. In this study using a saturated sample because the population is not more than 100 people, the authors took 100% of the population. The data analysis method used in this study is quantitative data analysis using multiple linear regression analysis. The tests used in this study are the F test and t test. The results of this study indicate that simultaneously the work environment, occupational health and safety (K3) have a positive-significant effect on the work productivity of employees in the production division of PT Mega Prakarsa Engineering Indonesia Sidoarjo. And based on the results of the partial test (TEST) the variables Work environment, occupational health and safety (K3) have a significant positive effect on the work productivity..Keywords: Work Environment, Occupational Health and Safety (K3) and Work Productivity